Education and Digital Media as Effective Approaches to Mental Health Literacy - Azis, Erina Widiyanti; Kurniati, Yessy (Unified Health Critical Research, 2025)
Mental health is an essential aspect of an individual's life that affects adaptability to stress, productivity and overall well-being. Improving mental health literacy is an important preventive strategy in dealing with psychological challenges, including promoting positive attitudes, self-efficacy, and help-seeking behavior. This study aims to identify educational and digital technology-based interventions and evaluate their effectiveness in improving mental health literacy. The method used was a traditional literature review of ten relevant scientific articles, obtained through a rigorous selection process from PubMed and Google Scholar databases. The initial search yielded 1,524 articles from PubMed and 201 from Google Scholar. Articles were obtained using a combination of keywords such as “mental health promotion”, “intervention”, ‘adolescents’ and “mental health education”. The analysis showed that different forms of interventions, such as online trainings, mental health curricula, digital self-efficacy training, and audiovisual media, were effective in increasing understanding, positive attitudes, self-efficacy, and propensity to seek professional help. The success of interventions relies heavily on contextualized, interactive and active participation-based designs, as well as integration with social support. Therefore, the development of adaptive, inclusive, and sustainable intervention models is crucial in strengthening efforts to promote and prevent mental health problems.